Solvent and additive-free selective aerobic allylic hydroxylation of β-pinene catalyzed by metalloporphyrins - Xu, Shi-Chao; Zhu, Shou-Ji; Bi, Liang-Wu; Chen, Yu-Xiang; Wang, Jing; Lu, Yan-Ju; Gu, Yan; Zhao, Zhen-Dong (Chinese chemical letters, 2017)
Metallodeuteroporphyrins（MDPs） were employed as the catalysts for aerobic oxidation of β-pinene in absence of solvents and additives. Allylic hydroxylation products were found to be the main products from this protocol. The catalytic activity of MDPs with different metal nuclei and the influences of technological conditions on this reaction were investigated. This catalytic system has bright application prospect since only eco-friendly and readily available dioxygen were needed.